Housing Governance in a Time of Financialization. A Comparative Analysis of Zurich, Birmingham and Lyon. - Zwicky, Roman (vdf, 2021)
In recent years, the financialization of housing has become a major challenge to many cities across the globe, not the least because it tends to favor the interests of global finance over the needs of residents. Based on three case studies in the city regions of Zurich, Birmingham and Lyon, the present investigation analyzes the interplay of housing governance and policies over the past 20 years against the backdrop of the financialization of housing.
Keywords: Kommunale Wohnungspolitik; Sozialer Wohnungsbau; Öffentlicher Wohnungsbau; Wohnungsprivatisierung; Urban Governance; Wohnraumversorgung; Fallstudie; Städtevergleich; Internationaler Vergleich; Bezahlbarer Wohnraum; Finanzialisierung